A ruthenium-based catalyst for the preferential oxidation of carbon monoxide in a hydrogen-rich gas and a method for its preparation

CN122974309APending Publication Date: 2026-10-27ZHEJIANG INST OF TIANJIN UNIV (SHAOXING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311496904.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

相对其它贵金属催化剂,钌基催化剂价格较低,在一氧化碳优先氧化具有较好的活性,但是催化剂存在低温活性较差和消除CO的温度范围较窄的问题

Benefits of technology

[0020]与现有技术相比,本发明以酸刻蚀方法处理制得氧化铝,对氧化铝的氧空位进行有效调控。以氧化铝为载体,通过化学还原法制备催化剂,使活性组分钌高度分散,加之Al2O3-A载体具有更丰富的表面氧空位缺陷,本发明提供的催化剂具有更强的金属-载体相互作用。与未处理Al2O3负载的Ru基催化剂相比,本发明提供的催化剂由于Ru物种与载体的相互作用增强,Ru物种高度分散,催化剂表现出优异的一氧化碳优先氧化反应性能,可在很宽的温度范围内完全消除CO,使H2适用于PEMFC的应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974309A_ABST
    Figure CN122974309A_ABST
Patent Text Reader

Abstract

The application discloses a ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas and a preparation method thereof. The catalyst comprises a metal ruthenium active component and an alumina carrier. The content of ruthenium is 0.01-5wt% based on the total mass of the ruthenium-based catalyst, and the balance is the carrier. The alumina is subjected to acid etching treatment to construct oxygen vacancy defects on the surface of the alumina. The catalyst with different ruthenium contents is prepared by a chemical reduction method with the alumina as the carrier. The catalyst is applied to the preferential oxidation reaction of carbon monoxide in hydrogen-rich gas, and shows excellent reaction activity and stability and a relatively wide carbon monoxide complete conversion temperature window. The catalyst has the advantages of simple preparation process, low raw material cost, easy repetition, good stability and significantly improved catalytic activity of the preferential oxidation of carbon monoxide, and has a good prospect for promoting the wide application of proton exchange membrane fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to an alumina-supported ruthenium catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas and its preparation method. Background Technology

[0002] Proton exchange membrane fuel cells (PEMFCs) offer advantages such as flexible size, low operating temperature, stable operation, and zero pollution, making them promising for applications in home power supply and power supply for new energy clean-energy vehicles in the transportation sector. PEMFCs use pure hydrogen and air as fuel, making them highly efficient devices for utilizing hydrogen energy. Currently, H2 produced from hydrocarbon reforming contains trace amounts of CO, which can poison the platinum electrodes of PEMFCs and reduce battery life. Therefore, the CO content must be reduced to an acceptable level (below 10 ppm) to ensure that H2 meets the stringent requirements for PEMFC applications.

[0003] Preferential oxidation of carbon monoxide (CO) is an effective and economical pathway to eliminate trace amounts of CO from H2. Currently, CO preferential oxidation catalysts are mainly gold-based, platinum-based, ruthenium-based, and copper-based catalysts. Compared to other precious metal catalysts, ruthenium-based catalysts are less expensive and exhibit good activity in CO preferential oxidation; however, they suffer from poor low-temperature activity and a narrow temperature range for CO elimination. Therefore, developing a ruthenium-based CO preferential oxidation catalyst with excellent low-temperature activity, low precious metal loading, and a wide CO complete conversion temperature window is of great significance for hydrogen energy utilization and the development of PEMFCs (Polymerized Elementary Chemical Fuels). Summary of the Invention

[0004] The purpose of this invention is to provide a ruthenium-based catalyst for the preferential oxidation of carbon monoxide in hydrogen-rich gas and its preparation method. The catalyst has the characteristics of high and low temperature activity, a wide temperature window for complete CO conversion, and high stability. The method is simple and highly reproducible.

[0005] The technical objective of this invention is achieved through the following technical solution.

[0006] A ruthenium-based catalyst for the preferential oxidation of carbon monoxide in hydrogen-rich gas and its preparation method are disclosed. The support is prepared by acid etching, and the catalyst is synthesized by chemical reduction. The catalyst consists of a ruthenium active component and an alumina support. The ruthenium content, based on the total mass of the catalyst, is greater than 0.01 wt% and less than or equal to 5 wt%, preferably 0.3–5 wt%. The process is carried out according to the following steps:

[0007] Step 1: Disperse the ruthenium precursor in water to form a homogeneous solution, add the pretreated alumina support, stir to form a homogeneous suspension, and then add a reducing agent to obtain a suspension; the ruthenium precursor is ruthenium trichloride, ruthenium nitrite or ruthenium acetate, the molar ratio of reducing agent to metallic ruthenium is (1-4):1, and the reducing agent is sodium borohydride, potassium borohydride or hydrazine hydrate; disperse γ-alumina in nitric acid aqueous solution to form a suspension, after heating and stirring, perform solid-liquid separation and washing and drying until the pH value is 7 to obtain the pretreated alumina support;

[0008] In step 1, mechanical or magnetic stirring is selected, and the stirring speed is 300-800 revolutions per minute.

[0009] In step 1, after adding the pretreated alumina carrier, the stirring time is 0.5-6 hours, preferably 1-3 hours.

[0010] In step 1, after adding the reducing agent, the reaction time is 1-5 hours.

[0011] In step 1, the concentration of the nitric acid aqueous solution is 0.1-1 mol / mL. -1 The volume is 20-100mL.

[0012] In step 1, heating is performed using either oil bath heating or water bath heating, with a heating temperature of 30-90℃ and a heating time of 1-12 hours. Stirring is performed using either mechanical stirring or magnetic stirring, with a stirring speed of 100-500 revolutions per minute.

[0013] In step 1, the drying temperature is 60-120℃ and the drying time is 4-24h.

[0014] Step 2: The suspension obtained in Step 1 is subjected to solid-liquid separation, washed and dried, and then calcined. After calcination, it is naturally cooled to room temperature to obtain a ruthenium-based catalyst, or it is calcined and then reduced, and after reduction, it is naturally cooled to room temperature to obtain a ruthenium-based catalyst.

[0015] During calcination, the calcination temperature is 200-500℃, the calcination time is 1-5 hours, and the calcination atmosphere is air or an inert protective gas. During reduction, the reduction temperature is 200-400℃, the reduction time is 1-5 hours, and the reduction atmosphere is a mixture of hydrogen and an inert protective atmosphere or a mixture of carbon monoxide and an inert protective atmosphere. In the mixture of hydrogen and an inert protective atmosphere, the volume percentage of hydrogen is 8-12%; in the mixture of carbon monoxide and an inert protective atmosphere, the volume percentage of carbon monoxide is 5-10%.

[0016] In step 2, the inert protective gas is nitrogen, helium, or argon.

[0017] In step 2, during calcination, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the calcination temperature, which is 200-500℃, and the calcination time is 2-5 hours. After calcination, the temperature is allowed to cool naturally to room temperature. During reduction, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the reduction temperature, which is 200-400℃, and the reduction time is 0.5-3 hours. After reduction, the preferential oxidation reaction of carbon monoxide in hydrogen-rich gas is carried out directly.

[0018] The catalyst described in this invention exhibits superior low-temperature activity and high stability in the preferential oxidation of carbon monoxide in hydrogen-rich gas, and can effectively eliminate CO over a wide temperature range.

[0019] In the hydrogen-rich gas, the volume percentages of each gas are 1% CO, 1% O2, 50% H2, and 48% N2, and the temperature range is 70–210 degrees Celsius.

[0020] Compared with existing technologies, this invention uses acid etching to prepare alumina, effectively controlling the oxygen vacancies in the alumina. Using alumina as a support, a catalyst is prepared via chemical reduction, resulting in high dispersion of the active component ruthenium. Furthermore, the Al2O3-A support has abundant surface oxygen vacancy defects, leading to stronger metal-support interactions in the catalyst provided by this invention. Compared to untreated Al2O3-supported Ru-based catalysts, the catalyst provided by this invention exhibits superior preferential carbon monoxide oxidation performance due to enhanced Ru species-support interactions and high Ru species dispersion. It can completely eliminate CO over a wide temperature range, making H2 suitable for PEMFC applications. Attached Figure Description

[0021] Figure 1 The images show the LT-EPR spectra of the catalysts prepared in Example 5 and Comparative Example 1.

[0022] Figure 2 The above are the H2-TPR curves of the catalysts prepared in Example 5 and Comparative Example 1.

[0023] Figure 3 The XRD patterns are those of the catalysts prepared in Example 5 and Comparative Example 1.

[0024] Figure 4 The images show the in-situ XPS spectra of the catalysts prepared in Example 5 and Comparative Example 1.

[0025] Figure 5 The images show TEM characterizations of the catalysts prepared in Example 5 and Comparative Example 1. Detailed Implementation

[0026] The technical solution of the present invention will be further described below with reference to specific embodiments.

[0027] Example 1

[0028] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (0.1mol / mL). -1 In a mixture of water and water, a suspension is formed by stirring until homogeneous. The resulting suspension is then vigorously stirred at 30°C for 1 hour. After stirring and cooling to room temperature, the suspension is filtered or centrifuged to obtain a solid material, which is then washed. The resulting solid is dried in an oven at 100°C for 4 hours to obtain the carrier Al2O3-Al.

[0029] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.01 wt% (mass of metallic Ru / sum of the masses of metallic Ru and the support), weigh 0.0001 g of nitrosylruthenium nitrate precursor with a metallic Ru content, dissolve it in 70 mL of water, and stir until homogeneous. Weigh 0.9999 g of Al₂O₃-Al powder and add it to the mixed solution, stirring to form a homogeneous suspension. Weigh potassium borohydride with a molar ratio of 1 to the metallic Ru, dissolve it in water to form a solution, and add this solution to the above suspension. Heat and stir at 60 °C for 3 h. The suspension is filtered or centrifuged to obtain a solid material, which is then washed. The obtained solid is dried in a 70 °C oven for 12 h, and then calcined in a tube furnace at 200 °C in air atmosphere for 3 h to obtain the catalyst 0.01Ru / Al₂O₃-Al.

[0030] The catalyst was used for the preferential oxidation of carbon monoxide in hydrogen-rich gas. 0.1 g of the catalyst (40-60 mesh) prepared in Example 1 was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was: 1% CO, 1% O2, 50% H2, and 48% N2 (this gas composition simulates the gas composition in a proton exchange membrane fuel cell, by volume percentage). The reaction temperature was 70-210℃ (the operating temperature of a proton exchange membrane fuel cell is approximately 80-180℃; to characterize the performance of the catalyst of this invention, the upper and lower limits of this reaction temperature range were appropriately expanded). The mass hourly space velocity (MSV) was 60000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.01Ru / Al2O3-Al-R200 reached its highest value of 79% at 210℃.

[0031] Example 2

[0032] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 90°C for 12 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 120°C for 24 hours to obtain the carrier Al2O3-A2.

[0033] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.05 wt%, ruthenium acetate precursor with a Ru content of 0.0005 g was weighed and dissolved in 70 mL of water, and stirred until homogeneous. 0.9995 g of Al₂O₃-A₂ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Hydrazine hydrate with a molar ratio of 4 to Ru was weighed, dissolved in water to form a solution, and added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 500 °C under a nitrogen atmosphere for 3 h to obtain catalyst 0.05Ru / Al₂O₃-A₂.

[0034] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 2, which was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.05Ru / Al2O3-A2-R200 reached 100% at 170℃, and 100% CO conversion was achieved in the temperature range of 170-210℃.

[0035] Example 3

[0036] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0037] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.1 wt%, ruthenium trichloride precursor with a Ru content of 0.001 g was weighed and dissolved in 70 mL of water, and stirred until homogeneous. 0.999 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain the catalyst 0.1Ru / Al₂O₃-A₃.

[0038] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 3, which was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.1Ru / Al2O3-A3 reached 100% at 150℃, and 100% CO conversion was achieved in the temperature range of 150-210℃.

[0039] Example 4

[0040] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0041] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.3 wt%, 0.003 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, and stirred until homogeneous. 0.997 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain the catalyst 0.3Ru / Al₂O₃-A₃.

[0042] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 4, which was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.3Ru / Al2O3-A3 reached 100% at 110℃, and 100% CO conversion was achieved in the temperature range of 110-210℃.

[0043] Example 5

[0044] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0045] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.5 wt%, 0.005 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, and stirred until homogeneous. 0.995 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain the catalyst 0.5Ru / Al₂O₃-A₃.

[0046] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 5, packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.5Ru / Al2O3-A3 reached 100% at 100℃, and 100% CO conversion was achieved in the temperature range of 100-210℃.

[0047] Example 6

[0048] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0049] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.5 wt%, 0.005 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, then stirred until homogeneous. 0.995 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain the catalyst 0.5Ru / Al₂O₃-A₃. The catalyst was reduced at 200°C for 1 hour in a CO / N2 atmosphere (5% CO, 95% N2 by volume) to obtain 0.5Ru / Al2O3-A3-R200 (reduction temperature 200°C).

[0050] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 6, packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.5Ru / Al2O3-A3-R200 reached 100% at 100℃, and 100% CO conversion was achieved in the temperature range of 100-210℃.

[0051] Example 7

[0052] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0053] Preparation of Ru-based catalyst: Based on a theoretical loading of 1.0 wt%, 0.015 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, then stirred until homogeneous. 0.985 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 70 °C for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain catalyst 1.5Ru / Al₂O₃-A₃. The catalyst was reduced at 400 °C for 1 h in an H2 / N2 atmosphere (8% H2, 95% N2 by volume) to obtain 1.5Ru / Al2O3-A3-R400.

[0054] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 7, packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 1.5Ru / Al2O3-A3-R400 reached 100% at 90℃, and 100% CO conversion was achieved in the temperature range of 90-210℃.

[0055] Example 8

[0056] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0057] Preparation of Ru-based catalyst: Based on a theoretical loading of 3.0 wt%, 0.03 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, and stirred until homogeneous. 0.97 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in a 70 °C oven for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain catalyst 3.0Ru / Al₂O₃-A₃. This catalyst was reduced at 200 °C for 1 h in an H₂ / N₂ atmosphere to obtain 3.0Ru / Al₂O₃-A₃-R₂00.

[0058] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 8, which was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 3.0Ru / Al2O3-A3-R200 reached 100% at 80℃, and 100% CO conversion was achieved in the temperature range of 80-210℃.

[0059] Example 9

[0060] Preparation of the support: Weigh 1g of commercial Al2O3 and slowly add it to 40mL of HNO3 solution (1mol / mL). -1 In a mixture of water and water, a suspension was formed by stirring until homogeneous. The resulting suspension was then vigorously stirred at 60°C for 4 hours. After stirring and cooling to room temperature, the suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in an oven at 100°C for 12 hours to obtain the carrier Al2O3-A3.

[0061] Preparation of Ru-based catalyst: Based on a theoretical loading of 5.0 wt%, 0.05 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, then stirred until homogeneous. 0.95 g of Al₂O₃-A₃ powder was weighed and added to the mixed solution, and stirred to form a homogeneous suspension. Sodium borohydride with a molar ratio of 1.5 to Ru was weighed and dissolved in water to form a solution, which was then added to the above suspension. The mixture was heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in a 70 °C oven for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain catalyst 5.0Ru / Al₂O₃-A₃. This catalyst was reduced at 200 °C for 1 h in an H₂ / N₂ atmosphere to obtain 5.0Ru / Al₂O₃-A₃-R₂00.

[0062] The catalyst used in the preferential oxidation of carbon monoxide was 0.1 g of the catalyst (40-60 mesh) prepared in Example 9, packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was 1% CO, 1% O2, 50% H2, and 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60,000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 5.0Ru / Al2O3-A3-R200 reached 100% at 80℃, and 100% CO conversion was achieved in the temperature range of 70-210℃.

[0063] Comparative Example 1

[0064] Preparation of Ru-based catalyst: Based on a theoretical loading of 0.5 wt%, 0.05 g of ruthenium trichloride precursor with a Ru content was weighed and dissolved in 70 mL of water, stirred to form a homogeneous mixture. 0.95 g of commercial Al₂O₃ powder was weighed and added to the mixed solution, stirred to form a homogeneous suspension, and heated and stirred at 90 °C for 3 h. The suspension was filtered or centrifuged to obtain a solid material, which was then washed. The resulting solid was dried in a 70 °C oven for 12 h, and then calcined in a tube furnace at 300 °C under a nitrogen atmosphere for 3 h to obtain the catalyst 0.5Ru / Al₂O₃. This catalyst was reduced at 200 °C for 1 h in a H₂ / N₂ atmosphere to obtain 0.5Ru / Al₂O₃-R₂00.

[0065] The catalyst was used for the preferential oxidation of carbon monoxide. 0.1 g of the catalyst (40-60 mesh) prepared in Comparative Example 1 was packed into a fixed-bed quartz tube reactor. The reaction tube was 50 cm long and 8 mm in inner diameter. The feed gas composition for the preferential oxidation of carbon monoxide was: 1% CO, 1% O2, 50% H2, 48% N2. The reaction temperature was 50-210 °C, and the mass hourly space velocity (HHSV) was 60000 mL·h. -1 ·g cat -1 The feed gas and reaction tail gas were analyzed online using an Agilent 7890A gas chromatograph. As shown in Table 1, the CO conversion rate of 0.5Ru / Al2O3-R200 reached 100% at 150℃, and 100% CO conversion was achieved in the temperature range of 150-210℃.

[0066] LT-EPR testing was performed to characterize the changes in the defect structure of the samples. Figure 1 As can be seen, both supports exhibit an EPR signal at g = 2.004, which originates from unpaired single electrons at oxygen vacancies. Compared to untreated alumina (Al2O3), the acid-etched Al2O3-A3 support shows a higher intensity EPR signal (i.e., electron paramagnetic resonance signal), indicating that it has a richer abundance of surface oxygen vacancies. This suggests that the acid etching strategy helps construct oxygen vacancy-like defects on the support surface. After Ru loading, the oxygen vacancy defect content on the 0.5Ru / Al2O3-A catalyst is significantly reduced compared to 0.5Ru / Al2O3, indicating that more Ru NPs on 0.5Ru / Al2O3-A are anchored to surface oxygen vacancies on Al2O3-A. Furthermore, the surface OH content (O 1s) of the catalyst decreases in the following order: 0.5Ru / Al2O3 > 0.5Ru / Al2O3-A, indicating that Ru NPs on Ru / Al2O3 are mainly anchored to surface OH groups on the support. Therefore, the differences in metal-support interaction (MSI) on catalysts stem from the different binding modes between the metal and the support. Among them, the oxygen vacancies on the support of 0.5Ru / Al2O3-A are beneficial to enhancing MSI, thereby promoting its CO-PROX reaction performance.

[0067] from Figure 2The H2-TPR curves of the catalyst show that, compared with the untreated Al2O3-supported Ru-based catalyst (Ru / Al2O3-A), the reduction temperature of the Al2O3-A3-supported Ru-based catalyst (Ru / Al2O3-A) is higher, indicating that the catalyst provided by this invention has stronger metal-support interaction. The reduction peaks at 50-220℃ (Peak-1) are attributed to the reduction of ruthenium oxide species, while the reduction peaks at 300-600℃ (Peak-2) are attributed to the reduction of active oxygen species on the support surface. The peak area of ​​Peak-2 on Ru / Al2O3 is larger than that on Ru / Al2O3-A, indicating that there are more surface hydroxyl groups on the Ru / Al2O3 surface. Compared with the Ru / Al2O3 catalyst, the ruthenium oxide species (Peak-1) of the Ru / Al2O3-A catalyst are reduced at a higher temperature, indicating that it has stronger MSI. This is attributed to the enhanced interaction between Ru species on the catalyst and the support caused by acid etching treatment, resulting in Ru being more firmly anchored on the γ-Al2O3 support. These results further confirm that acid etching of the support can remove some hydroxyl groups from its surface and form oxygen vacancies, thereby regulating the interaction between Ru species and the support. Combined with the activity data in Table 1, it can be seen that, compared with the untreated Al2O3-supported Ru-based catalyst, the catalyst provided by this invention exhibits excellent preferential carbon monoxide oxidation performance due to the enhanced interaction between Ru species and the support and the high dispersion of Ru species. It can completely eliminate CO over a wide temperature range, making H2 suitable for PEMFC applications.

[0068] exist Figure 3 In the XRD patterns, (a) shows the XRD patterns of Al2O3-A3 and Al2O3. It can be observed that both supports exhibit characteristic diffraction peaks belonging to different crystal planes of γ-Al2O3 (JCPDS#10-0425), indicating that acid etching did not affect the crystal structure of the supports. (b) shows the XRD pattern of the catalyst. It can be seen that after Ru loading, the crystal phase of the support did not change significantly, indicating that the support structure is stable and Ru did not disrupt the phase composition of the support, thus ruling out the influence of the exposed γ-Al2O3 crystal plane on the catalytic performance. Furthermore, no diffraction peaks related to Ru species were observed in the XRD pattern of the catalyst. This indicates a strong interaction between the support and Ru on the catalyst, resulting in a highly dispersed state of Ru NPs on the support surface, or that the particle size of the Ru NPs is below the detection limit of XRD.

[0069] exist Figure 4In the figures, (a) shows the XPS values ​​of the 0.5Ru / Al2O3 and 0.5Ru / Al2O3-A3 catalysts in the Ru 3d region, and (b) shows the XPS values ​​of the 0.5Ru / Al2O3 and 0.5Ru / Al2O3-A catalysts in the Ru 3p region. In (a), the characteristic peaks in the ranges of 279.6–280.3 eV and 281.3–281.6 eV are attributed to Ru, respectively. 0 Species and Ru δ+ Ru 3d of the species 5 / 2 Peak. Compared to 0.5Ru / Al2O3, the Ru 3d peak of 0.5Ru / Al2O3-A is higher. 5 / 2 The peak shifts towards lower binding energies, indicating that the support on it transfers more electrons to Ru. To eliminate the interference of C1s on the Ru3d peak fitting, the in-situ XPS spectrum of the catalyst in the Ru 3p region was tested. As can be seen from (b), the Ru 3p spectrum of the catalyst shows a similar trend in binding energy change as the Ru 3d spectrum. Combining the EPR and in-situ XPS results, it can be concluded that the oxygen vacancies in Al2O3-A can induce the construction of a stronger MSI in 0.5Ru / Al2O3-A, leading to the transfer of electrons from Al2O3-A to Ru and enhancing the electron-donating ability of Ru. According to literature reports, oxygen activation is a key step in CO oxidation. When noble metal nanoparticles have high electron density, they can enhance the adsorption and activation of oxygen by transferring electrons to oxygen. Based on the above results, it can be inferred that the superior low-temperature CO-PROX activity of 0.5Ru / Al2O3-A compared to 0.5Ru / Al2O3 can be attributed to the stronger oxygen adsorption and activation ability on the catalyst.

[0070] exist Figure 5 In the results, (a) and (c) show that the 0.5Ru / Al2O3 and 0.5Ru / Al2O3-A3 catalysts achieve the dispersion of metallic Ru on the support; (b) and (d) show that the metallic Ru particles of the 0.5Ru / Al2O3 and 0.5Ru / Al2O3-A3 catalysts are in the nanoscale, with particle sizes of 0.7±0.2nm and 0.5±0.1nm, respectively.

[0071] Table 1: List of catalysts' preferential carbon monoxide oxidation performance.

[0072]

[0073] Adjusting the process parameters according to the present invention can achieve the preparation of the catalyst of the present invention, and testing has shown that it exhibits performance substantially consistent with that of the present invention. The present invention has been described above as exemplary. It should be noted that any simple modifications, alterations, or other equivalent substitutions that can be made by those skilled in the art without creative effort, without departing from the core of the present invention, fall within the protection scope of the present invention.

Claims

1. A ruthenium-based catalyst for the preferential oxidation of carbon monoxide in hydrogen-rich gas, characterized in that, The support was prepared by acid etching, and the catalyst was synthesized by chemical reduction. The catalyst consisted of a ruthenium active component and an alumina support. The ruthenium content, based on the total mass of the catalyst, was greater than 0.01 wt% and less than or equal to 5 wt%, preferably 0.3–5 wt%. The process was carried out according to the following steps: Step 1: Disperse the ruthenium precursor in water to form a homogeneous solution, add the pretreated alumina support, stir to form a homogeneous suspension, and then add a reducing agent to obtain a suspension; the ruthenium precursor is ruthenium trichloride, ruthenium nitrite or ruthenium acetate, the molar ratio of reducing agent to metallic ruthenium is (1-4):1, and the reducing agent is sodium borohydride, potassium borohydride or hydrazine hydrate; disperse γ-alumina in nitric acid aqueous solution to form a suspension, after heating and stirring, perform solid-liquid separation and washing and drying until the pH value is 7 to obtain the pretreated alumina support; Step 2: The suspension obtained in Step 1 is subjected to solid-liquid separation, washed and dried, and then calcined. After calcination, it is naturally cooled to room temperature to obtain a ruthenium-based catalyst. Alternatively, after calcination, it is reduced and then naturally cooled to room temperature to obtain a ruthenium-based catalyst. During calcination, the calcination temperature is 200-500℃, the calcination time is 1-5 hours, and the calcination atmosphere is air or an inert protective gas. During reduction, the reduction temperature is 200-400℃, the reduction time is 1-5 hours, and the reduction atmosphere is a mixture of hydrogen and an inert protective atmosphere or a mixture of carbon monoxide and an inert protective atmosphere. In the mixture of hydrogen and an inert protective atmosphere, the volume percentage of hydrogen is 8-12%; in the mixture of carbon monoxide and an inert protective atmosphere, the volume percentage of carbon monoxide is 5-10%.

2. The ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 1, characterized in that, In step 1, mechanical or magnetic stirring is used, with a stirring speed of 300-800 rpm. After adding the pretreated alumina support, the stirring time is 0.5-6 hours, preferably 1-3 hours. After adding the reducing agent, the reaction time is 1-5 hours. The concentration of the nitric acid aqueous solution is 0.1-1 mol / mL. -1 The volume is 20-100mL.

3. The ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 1, characterized in that, In step 1, heating is performed using either oil bath or water bath, with a heating temperature of 30-90℃ and a heating time of 1-12 hours. Stirring is performed using either mechanical or magnetic stirring, with a stirring speed of 100-500 revolutions per minute. During drying, the drying temperature is 60-120℃ and the drying time is 4-24 hours.

4. The ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 1, characterized in that, In step 2, the inert protective gas is nitrogen, helium, or argon. During calcination, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the calcination temperature, which is 200-500℃. The calcination time is 2-5 hours, and the gas is allowed to cool naturally to room temperature after calcination. During reduction, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the reduction temperature, which is 200-400℃. The reduction time is 0.5-3 hours. After reduction, the carbon monoxide in the hydrogen-rich gas is preferentially oxidized directly.

5. A method for preparing a ruthenium-based catalyst for the preferential oxidation of carbon monoxide in hydrogen-rich gas, characterized in that, The support was prepared by acid etching, and the catalyst was synthesized by chemical reduction. The catalyst consisted of a ruthenium active component and an alumina support. The ruthenium content, based on the total mass of the catalyst, was greater than 0.01 wt% and less than or equal to 5 wt%, preferably 0.3–5 wt%. The process was carried out according to the following steps: Step 1: Disperse the ruthenium precursor in water to form a homogeneous solution, add the pretreated alumina support, stir to form a homogeneous suspension, and then add a reducing agent to obtain a suspension; the ruthenium precursor is ruthenium trichloride, ruthenium nitrite or ruthenium acetate, the molar ratio of reducing agent to metallic ruthenium is (1-4):1, and the reducing agent is sodium borohydride, potassium borohydride or hydrazine hydrate; disperse γ-alumina in nitric acid aqueous solution to form a suspension, after heating and stirring, perform solid-liquid separation and washing and drying until the pH value is 7 to obtain the pretreated alumina support; Step 2: The suspension obtained in Step 1 is subjected to solid-liquid separation, washed and dried, and then calcined. After calcination, it is naturally cooled to room temperature to obtain a ruthenium-based catalyst. Alternatively, after calcination, it is reduced and then naturally cooled to room temperature to obtain a ruthenium-based catalyst. During calcination, the calcination temperature is 200-500℃, the calcination time is 1-5 hours, and the calcination atmosphere is air or an inert protective gas. During reduction, the reduction temperature is 200-400℃, the reduction time is 1-5 hours, and the reduction atmosphere is a mixture of hydrogen and an inert protective atmosphere or a mixture of carbon monoxide and an inert protective atmosphere. In the mixture of hydrogen and an inert protective atmosphere, the volume percentage of hydrogen is 8-12%; in the mixture of carbon monoxide and an inert protective atmosphere, the volume percentage of carbon monoxide is 5-10%.

6. The method for preparing a ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 5, characterized in that, In step 1, mechanical or magnetic stirring is used, with a stirring speed of 300-800 rpm; after adding the pretreated alumina support, the stirring time is 0.5-6 hours, preferably 1-3 hours; after adding the reducing agent, the reaction time is 1-5 hours; the concentration of the nitric acid aqueous solution is 0.1-1 mol / mL. -1 The volume is 20-100mL.

7. The method for preparing a ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 5, characterized in that, In step 1, heating is performed using either oil bath or water bath, with a heating temperature of 30-90℃ and a heating time of 1-12 hours. Stirring is performed using either mechanical or magnetic stirring, with a stirring speed of 100-500 revolutions per minute. During drying, the drying temperature is 60-120℃ and the drying time is 4-24 hours.

8. A method for preparing a ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas according to claim 5, characterized in that, In step 2, the inert protective gas is nitrogen, helium, or argon. During calcination, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the calcination temperature, which is 200-500℃. The calcination time is 2-5 hours, and the gas is allowed to cool naturally to room temperature after calcination. During reduction, the temperature is increased from room temperature (20-30℃) at a rate of 1-10℃ per minute to the reduction temperature, which is 200-400℃. The reduction time is 0.5-3 hours. After reduction, the carbon monoxide in the hydrogen-rich gas is preferentially oxidized directly.

9. The application of the ruthenium-based catalyst for preferential oxidation of carbon monoxide in hydrogen-rich gas as described in any one of claims 1-4 in the catalytic preferential oxidation reaction of carbon monoxide in hydrogen-rich gas.

10. The application according to claim 9, characterized in that, In the hydrogen-rich gas, the volume percentages of each gas are 1% CO, 1% O2, 50% H2, and 48% N2, and the temperature range is 70–210 degrees Celsius.